Extent of Adoption of Improved Pig Farming Practices by the Farmers and their Effective Determinants in North Eastern States of India - Singha, A. K.; Tripathi, A. K.; Jat, P. C.; Bordoloi, R.; Singha, J. K.; Devi, Merina (Indian Journal of Hill Farming, 2016)
This study to determine the extent of adoption of pig farming practices in North Eastern Region of India was conducted in 13 purposively selected KVK districts in the region with 130 sample size from each adopted and non-adopted villages selected through proportionate random sampling. Data collection from the selected respondents was made with the help of pre-tested structured schedule through personal interview method. The study reveals that over half of the respondents in KVKs adopted villages had medium level of adoption of improved pig farming practices, while majority with over half of the total respondents in non-adopted villages were found poor adoption level of the same piggery practices. Respondents of non-beneficiary farmers was found little adoption of specific recommendations of selected farming practices like housing, breeding, feeding and health care as shown by their corresponding mean values compared to beneficiary farmers.